2015
DOI: 10.1139/juvs-2015-0005
|View full text |Cite
|
Sign up to set email alerts
|

Aerial photography collected with a multirotor drone reveals impact of Eurasian beaver reintroduction on ecosystem structure

Abstract: Beavers are often described as ecological engineers with an ability to modify the structure and flow of fluvial systems and create complex wetland environments with dams, ponds, and canals. Consequently, beaver activity has implications for a wide range of environmental ecosystem services including biodiversity, flood risk mitigation, water quality, and sustainable drinking water provision. With the current debate surrounding the reintroduction of beavers into the United Kingdom, it is critical to be able to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 39 publications
1
51
0
1
Order By: Relevance
“…In particular, UAV equipped with consumer-grade onboard system camera and different sensors have been used to estimate tree counts, tree heights and crowns measurements due to its low cost and faster performance compared to traditional methods [22,23,[69][70][71][72][73][74]. In this paper, we present a simplified framework for automated ITD from UAV-SfM derived CHM based on algorithms designed for LiDAR data processing.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, UAV equipped with consumer-grade onboard system camera and different sensors have been used to estimate tree counts, tree heights and crowns measurements due to its low cost and faster performance compared to traditional methods [22,23,[69][70][71][72][73][74]. In this paper, we present a simplified framework for automated ITD from UAV-SfM derived CHM based on algorithms designed for LiDAR data processing.…”
Section: Discussionmentioning
confidence: 99%
“…In the presented figures this constructed pond is displayed as Pond 8a and has since expanded to cover the area labelled 8b, which are analysed herein together as pond 8. Beaver activity has created a complex wetland environment, dominated by ponds, dams and an extensive canal network (DWT, 2013; Puttock et al ., 2015). The age of ponds is detailed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…We showed that high-resolution UAS imagery revealed fine-scale wetland habitat cover details that were not detected by ground surveys (Chabot and Bird 2013), leading to conclusions about breeding habitat associations of the threatened least bittern (Ixobrychus exilis) that may otherwise have been overlooked using strictly conventional data collection methods (Chabot et al 2014). Puttock et al (2015) report on the use of multirotor UAS imagery to assess the impact of Eurasian beaver (Castor fiber) reintroduction on wetland ecosystem structure. Several other studies have focused on the ability to automatically or semi-automatically classify vegetation in high-resolution UAS imagery of wetlands and bogs (Kalacska et al 2013;Knoth et al 2013;Husson et al 2014a;Zweig et al 2015).…”
Section: Wetland Riparian and Coastal Habitatsmentioning
confidence: 97%